DRILLING COLUMN FIXING: BOUNDARY DEFINITION AND SUPERVISORY FORMS, RECOMMENDATIONS FOR THEIR DESTRUCTION BEFORE YOU TAKE SURPRISES - Левчук, Катерина Григорівна; Векерик, Василь Іванович; Мойсишин, Василь Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The expediency of using the acoustic method for determining the borders between the picking of a drilling tool and sections with different degrees of pipe bending is substantiated. The method of determination of restraining force is developed on the basis of contact pressure data between the rock and the captured pipes. Frictional forces that prevent the drilling column movement during its release are determined. Recommendations for preventing different groups of hijacking are systematized. The construction of the device which allows straightening the trunk with complications that arise during drilling of wells is proposed.